HUBUNGAN ANTARA FAKTOR PREDISPOSISI DAN FAKTOR PENGUAT DENGAN PERILAKU TIDAK AMAN PADA TENAGA KESEHATAN DI PUSKESMAS X KOTA SEMARANG - Arief Noviandhi Surbakti; Siswi Wijayanti; Yuliani Setyaniingsih (Jurnal Kesehatan Masyarakat (Undip), 2018)
Health care workers have a high risk of contaminating infectious diseases due to work time, especially when providing health services, impaled by contaminated needles from the blood of patients, exposed by blood splashes, body fluids, and secretions from patients. The aim of this study was to analyze the relationship between predisposing factors and reinforcing factors with the unsafe behavior among health workers in Public Health Center X in Semarang. The dependent variable in this research was unsafe behavior and the independent variable was predisposing factors including the perception of health care workers toward their work, the work attitude of health care workers toward their work, work motivation, and reinforcing factors including supervision of the head of public health center and occupational safety and health promotion. The type of this research was explanatory research with a cross-sectional design. The population in this study were 32 health care workers including medical personnel, nursing staff, and medical engineering personnel with total population sampling method. Data was collected using interview method guided by questionnaire. Statistical analysis was conducted by Rank Spearman test. The results showed that perception (sig = 0,022), attitude (sig = 0,022), work motivation (sig = 0,000), and supervision of the head of public health center (sig = 0,033) had relationship with unsafe behavior. While the occupational safety and health promotion (sig = 0.495) had no relationship with unsafe behavior. Public Health Center ought to have special data toward the incidence of occupational accidents, delivers occupational safety and health messages routinely in every one week, gives sign about the PPE that must be used in the workplace and how to use PPE properly, and also provides a sign that indicates the accident-prone areas such as a slippery floor.